Análise e propostas para o espectro diferencial: estimação DOA através de normas matriciais no método SEAD - Kunzler, Jonas Augusto (2015)
New technologies that have emerged from the transistor advent enabled digital signal processing techniques were aggregated to systems operated or partially in analog improving performance of these systems. Added to this the use of sensor arrangements which made it possible to identify the directions of signals of interest and are used in critical areas of knowledge, such as in tracking radar systems; in astronomy; in sonar systems; mobile communications; the estimation of direction of arrival; in seismology and medical diagnosis and treatment. This work aims to study specific features of an estimation method of direction of arrival based on a linear array of sensors with special attention to mobile communications. Some methods have been proposed in order to get the position of a source of electromagnetic waves and can cite the MUSIC, the MODEX and SEAD, the latter of fundamental importance to this work because it is the basis of conducted research and because it is a new method, lacked further clarification with regard to the differential spectrum, their origin, meaning and importance, as well as obtaining an analytical expression to describe their conduct on the variables that compose the system. Based on eigenvalue decomposition of the correlation matrix has been observed that the differential spectrum is basically a matrix norm calculation, with the largest eigenvalue of the matrix is ​​also standard 2-induced vector. It was proposed to use the Frobenius norm which is simpler to be computed, and consequently requires less computational effort. Moreover, the behavior of the angular spectrum calculated using the Frobenius norm is fully described by the sum of cosines with the formulation described for each part which composes the calculation of the standard. Through this outcome was possible to analyze aspects related to angular resolution, the number of signal sources, the number of sensors, the influence of noise and the correlation between sources.